An Assessment of Rotifer Diversity in Tikhol Dam, Parner Tehsil, Ahmednagar, MS, India - Zaware R.V,; Harkal A. D, (The Bioscan, 2025)
The present research explores the diversity and dispersal of rotifer fauna inside Tikhol Dam at Tikhol, District Ahilyanagar (Ahmednagar). Seasonal sampling was conducted at multiple sites across the dam for a year and species identification was performed using standard taxonomic keys. The study recorded a rich diversity of rotifers, with species composition slightly varying across seasons and sampling sites—the significant seasonal variation in rotifer populations, with peak diversity observed at the time of winter period. The genus Brachionus (family Brachionidae) dominated the rotifer community, indicating a freshwater ecosystem with moderate to high nutrient levels (mesotrophic to eutrophic conditions). A total 5 number of genera with 12 species were reported from the dam.